Pelaksanaan Asas Praduga Tak Bersalah - Niko Saputra; Haryadi Haryadi; Tri Imam Munandar (PAMPAS: Journal of Criminal Law, 2022)
This article aims to find out and understand the implementation of the principle of the presumption of innocence in the jurisdiction of the Jambi City Police and to find out and analyze the obstacles to the implementation of the principle of the presumption of innocence in the jurisdiction of the Jambi City Police. The results of this study show that: 1) The implementation of the principle of presumption of innocence in the jurisdiction of the Jambi City Police is still not fully running well, because there are still perpetrators of criminal acts who are judged by the masses. 2) Public awareness of the law is still relatively low so that vigilante behavior by the community is still common. The author's suggestions to law enforcement officers 1) In order to be able to socialize more about the importance of implementing the principle of the presumption of innocence in society so that a good judicial process is realized in accordance with applicable legal provisions and the community 2) In order to increase awareness of the law so that vigilante behavior can be avoided and avoided from legal snares that can befall people who carry out vigilante or eigenrichting behavior. Â  ABSTRAK Artikel ini bertujuan untuk mengetahui dan memahami mengenai Pelaksanaan Asas Praduga Tak Bersalah di Wilayah Hukum Polres Kota Jambi dan untuk mengetahui dan menganalisis mengenai kendala pelaksanaan Asas Praduga Tak Bersalah di Wilayah Hukum Polres Kota Jambi. Hasil Penelitian ini memperlihatkan bahwa: 1) Pelaksanaan asas praduga tak bersalah di wilayah hukum Kepolisian Resor Kota Jambi masih belum sepenuhnya berjalan baik, karena masih ditemukannya pelaku tindak pidana yang dihakimi oleh massa. 2) Kesadaran masyarakat akan hukum masih terbilang rendah sehingga perilaku main hakim sendiri yang dilakukan masyarakat masih sering terjadi. Saran penulis kepada aparat penegak hukum 1) Agar dapat lebih lagi dalam mensosialisasikan mengenai pentingnya pelaksanaan asas praduga tak bersalah di masyarakat sehingga terwujud suatu proses peradilan yang baik sesuai ketentuan hukum yang berlaku dan masyarakat 2) Agar dapat meningkatkan kesadaran akan hukum sehingga perilaku main hakim sendiri dapat dihindari dan terhindar dari jerat hukum yang dapat menimpa orang orang yang melakukan perilaku main hakim atau eigenrichting.